A reversible colorimetric chemosensor for naked-eye detection of copper ions using poly (aspartic acid) nanofibrous hydrogel. (December 2015) - Zhang, Caidan; Wan, Lynn Yuqin; Wu, Shaohua; Wu, Dequn; Qin, Xiaohong; Ko, Frank
Abstract: A novel, biodegradable colorimetric chemosensor for Cu 2+ ions detection in aqueous water was designed using poly (aspartic acid) nanofibrous hydrogel, based on the strong complexation ability of poly (aspartic acid) nanofibrous hydrogel and the specific color change phenomena of biuret reaction. The poly (aspartic acid) nanofibrous hydrogel sensor exhibited high sensitivity and selectivity toward Cu 2+ ions over other competing ions with a detection limit of 0.01 mg/L. Furthermore, the poly (aspartic acid) nanofibrous hydrogel sensor displayed a sensitive colorimetric response in the presence of Cu 2+ ions according to the pH values it exposed to. The on–off–on color switching behavior upon pH alternation between 14 and 1 illustrated an excellent reversible color change. This low-cost, biodegradable and reversible sensor possessed a promising application for practical Cu 2+ ions detection in real water samples and provided a new insight into the design of colorimetric sensor based on nanofibrous hydrogel. Graphical abstract: Highlights: A colorimetric sensor based on poly (aspartic acid) nanofibrous hydrogel was designed. The biuret reaction was employed for Cu 2+ ions detection. The detection limit was as low as 0.01 mg/L. The sensor was biodegradable and reversible.